2001
DOI: 10.2337/diabetes.50.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Histamine H1-Receptor Attenuates Regulatory Effects of Leptin on Feeding, Adiposity, and UCP Family in Mice

Abstract: Histamine neurons are widely distributed in the brain and suppress food intake through the histamine H 1 receptor (H 1 -R) in the hypothalamus. To examine the role of neuronal histamine in leptin signaling pathways, we investigated the effects of H 1 -R knockout (H1KO) mice on both food intake and mRNA expressions of uncoupling proteins (UCPs) as regulated by leptin, and concomitantly on basal changes in both expression of hypothalamic neuropeptides and diet-induced fat deposition in adipose tissues. H1KO mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 45 publications
6
95
0
2
Order By: Relevance
“…Elevation of histamine levels in the brain, by either direct administration of histamine or systemic administration of its precursor, histidine, results in appetite suppression, and a number of pharmacological studies have suggested the involvement of H1 receptors (5,8,13,(15)(16)(17)(18). This finding was confirmed by this study, which shows that inhibition of histamine release by ␣-FMH increased appetite slightly at 4 h and significantly at 12 h. In contrast, comparable inhibition of histamine release by imetit resulted in appetite suppression, suggesting that imetit decreases appetite independently of histaminergic tone modulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of histamine levels in the brain, by either direct administration of histamine or systemic administration of its precursor, histidine, results in appetite suppression, and a number of pharmacological studies have suggested the involvement of H1 receptors (5,8,13,(15)(16)(17)(18). This finding was confirmed by this study, which shows that inhibition of histamine release by ␣-FMH increased appetite slightly at 4 h and significantly at 12 h. In contrast, comparable inhibition of histamine release by imetit resulted in appetite suppression, suggesting that imetit decreases appetite independently of histaminergic tone modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebroventricular administration of histamine consistently decreases appetite in several species (4). Mice with genes disrupted for histamine H1 receptor or histidine decarboxylase (HDC), a ratelimiting enzyme for histamine synthesis, are prone to becoming obese on a high-fat diet or at advanced age (5)(6)(7)(8). Furthermore, several antipsychotic drugs with high affinities for H1 receptors are known to cause weight gain in rodents and humans (9).…”
mentioning
confidence: 99%
“…This finding has subsequently been confirmed by others, [53][54][55] and is consistent with data demonstrating that histamine H 1 receptor antagonism promotes feeding in rodents and that H 1 knockout mice are prone to weight gain. [55][56][57] Recently, Kim et al 55 showed that atypical orexigenic antipsychotics selectively and potently stimulate hypothalamic adenosine monophosphate-activated protein kinase (AMP kinase), an enzyme involved in regulating food intake, 58 while reversing the actions of leptin, an anorexigenic hormone. This effect is mediated through the histamine H 1 receptor: clozapine augmentation of AMP kinase was abolished in H 1 knockout mice and the orexigenic potencies of various atypical antipsychotics were found to correlate with their affinity for the H 1 receptor, with olanzapine and clozapine having the highest affinities in animal models.…”
Section: Weight Gainmentioning
confidence: 99%
“…It has been reported that H 1 R antagonists play a crucial role in increasing appetite and obesity development [12,53], which were also observed in H 1 R knockout (KO) mice [51,54].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 99%